Surveying the Organization of Digital Contents in the Internet Environments Using Ontological Approaches - Sabah Hassan, Geehan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Ontology is a system for classifying human knowledge according to its objective characteristics and hierarchical relations through building clusters or that bear common characteristics. In digital environments, it is a mechanism that helps regulate a vast amount of information by achieving a complete link between sub-thematic concepts and their main assets. The purpose of this study is to survey the previously conducted studies that use ontology in organizing digital data on social networking sites, such as the search engines Yahoo, Google, and social networks as Facebook and their findings. Results have shown that all these studies invest ontology for the purpose of organizing digital content data, especially on the Internet sites.